2019
DOI: 10.1177/0957650919839583
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of aerodynamic forces on turbine blading by asymmetric layout of struts based on flow interaction between rotor-strut-volute

Abstract: The flows in the power turbine and nonaxisymmetric exhaust volute with struts are closely coupled and inherently unsteady for marine gas turbines, and the flow interactions between them have a significant influence on the rotor and strut blade aerodynamic force characteristics; however, the asymmetric flow interactions have not been taken into account properly in current turbine design approaches. This paper is a continuation of the previous work and aims to clarify effects of different symmetrical and asymmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…In addition, Gao et al 50 has adopted coupled unsteady calculations with the full-annulus computational domain to identify effects of various symmetrical and asymmetric layouts of struts on the unsteady flow interactions between the axial turbine and the nonaxisymmetric exhaust volute, as shown in Figures 8 and 9. 1,50 It attempts to seek an optimal layout of struts to exploit the mentioned asymmetric flow interactions to decrease the rotor and strut blade aerodynamic forces. The unsteady flow results shown in Figure 10 50 indicated that the level of aerodynamic force at specific frequencies on the turbine blade may be decreased by applying a proper distribution of asymmetric layout of struts.…”
Section: Design Optimization Of Exhaust Volutes Towards Improving the Turbine-volute Performancementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Gao et al 50 has adopted coupled unsteady calculations with the full-annulus computational domain to identify effects of various symmetrical and asymmetric layouts of struts on the unsteady flow interactions between the axial turbine and the nonaxisymmetric exhaust volute, as shown in Figures 8 and 9. 1,50 It attempts to seek an optimal layout of struts to exploit the mentioned asymmetric flow interactions to decrease the rotor and strut blade aerodynamic forces. The unsteady flow results shown in Figure 10 50 indicated that the level of aerodynamic force at specific frequencies on the turbine blade may be decreased by applying a proper distribution of asymmetric layout of struts.…”
Section: Design Optimization Of Exhaust Volutes Towards Improving the Turbine-volute Performancementioning
confidence: 99%
“…Figure 9. Backward looking front view of the exhaust volute showing three-dimensional layout of struts 50. …”
mentioning
confidence: 99%